Is Everyone Beating Around the Bush?: A Qualitative Study Examining the Status of Shared Decision-Making Between Veterans Affairs Providers and Surgical Patients in the ICU - M. Andrew Millis, MD, MPH; C. Ann Vitous, MA, MPH; Cara Ferguson, BS; Maedeh Marzoughi, BS; Erin Kim, BS; Sarah E. Bradley, PhD, MPH, CPH; Ashley Duby, MS; Pasithorn A. Suwanabol, MD, MS (Annals of Surgery Open)
Objective:. We sought to determine if and how providers use elements of shared decision-making (SDM) in the care of surgical patients in the intensive care unit (ICU). Background:. SDM is the gold standard for decision-making in the ICU. However, it is unknown if this communication style is used in caring for critically ill surgical patients. Methods:. Qualitative interviews were conducted with providers who provide ICU-level care to surgical patients in Veterans Affairs hospitals. Interviews were designed to examine end-of-life care among veterans who have undergone surgery and require ICU-level care. Results:. Forty-eight providers across 14 Veterans Affairs hospitals were interviewed. These participants were diverse with respect to age, race, and sex. Participant dialogue was deductively mapped into 8 established SDM components: describing treatment options; determining roles in the decision-making process; fostering partnerships; health care professional preferences; learning about the patient; patient preferences; supporting the decision-making process; and tailoring the information. Within these components, participants shared preferred tools and tactics used to satisfy a given SDM component. Participants also noted numerous barriers to achieving SDM among surgical patients. Conclusions:. Providers use elements of SDM when caring for critically ill surgical patients. Additionally, this work identifies facilitators that can be leveraged and barriers that can be addressed to facilitate better communication and decision-making through SDM. These findings are of value for future interventions that seek to enhance SDM among surgical patients both in the ICU and in other settings.